Early-Onset Schizophrenia Showed Similar but More Severe Olfactory Identification Impairment Than Adult-Onset Schizophrenia - Li, Ze-tian; Li, Shu-bin; Wen, Jin-feng; Zhang, Xiao-yuan; Hummel, Thomas; Zou, Lai-quan (Frontiers in Psychiatry, 2020)
Background: “Early-onset schizophrenia” (EOS) is defined as disease with onset before the age of 18 years. This subset of schizophrenia exhibits worse cognitive function and carries a worse prognosis than adult-onset schizophrenia (AOS). Olfactory impairment has been found in patients with schizophrenia-spectrum disorders. However, most research has focused on olfactory impairment in patients with AOS: olfactory function in EOS is not known. The aim of this study was to investigate the olfactory identification ability in EOS, and its relationship with negative symptoms. Methods: We compared olfactory function between two independent samples; 40 patients with EOS and 40 age- and sex-matched healthy controls (HCs); as well as 40 patients with AOS and 40 age- and sex-matched HCs. The University of Pennsylvania Smell Identification Test was administered. Results: The EOS group and AOS group exhibited worse olfactory identification ability than HCs; impairment correlated significantly with negative symptoms. Olfactory identification was worse in patients suffering EOS compared with those suffering AOS. Conclusion: Olfactory identification impairment may be a trait marker of schizophrenia.